2004
DOI: 10.1152/jn.00596.2004
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Control Arm Stiffness Under Static Conditions

Abstract: Darainy, Mohammad, Nicole Malfait, Paul L. Gribble, Farzad Towhidkhah, and David J. Ostry. Learning to control arm stiffness under static conditions. J Neurophysiol 92: 3344 -3350, 2004. First published July 28, 2004 doi:10.1152/jn.00596.2004. We used a robotic device to test the idea that impedance control involves a process of learning or adaptation that is acquired over time and permits the voluntary control of the pattern of stiffness at the hand. The tests were conducted in statics. Subjects were trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
68
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 20 publications
12
68
3
Order By: Relevance
“…Feedback responses to transient perturbations of endpoint position can be large (Krutky et al 2010;Perreault et al 2008), and protocols that use transient perturbations to estimate endpoint stiffness (Burdet et al 2001;Darainy et al 2004;Franklin et al 2007) may not be well-represented by our model. Deviations between our model predictions and stiffness estimates made using transient perturbations may be useful for beginning to assess reflex contributions to the regulation of endpoint stiffness.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Feedback responses to transient perturbations of endpoint position can be large (Krutky et al 2010;Perreault et al 2008), and protocols that use transient perturbations to estimate endpoint stiffness (Burdet et al 2001;Darainy et al 2004;Franklin et al 2007) may not be well-represented by our model. Deviations between our model predictions and stiffness estimates made using transient perturbations may be useful for beginning to assess reflex contributions to the regulation of endpoint stiffness.…”
Section: Discussionmentioning
confidence: 97%
“…Actively controlled mechanisms at a specific arm posture include the intrinsic properties of the muscles within the arm, which are dependent on their steady state or feedforward activation, and transient changes in muscle activation that may occur via feedback pathways such as stretch reflexes or voluntary responses to the imposed displacements. Although numerous studies have characterized the behavioral characteristics of endpoint stiffness (Burdet et al 2001;Darainy et al 2004;Franklin et al 2003;Franklin et al 2007;Gomi and Osu 1998;Perreault et al 2001;Tsuji et al 1995) and the feedback responses that may modulate this stiffness (Krutky et al 2010;Perreault et al 2008), few have directly assessed which muscle properties contribute most to the stiffness properties of an entire limb. This knowledge is essential for understanding how changes in neural activation alter limb stiffness or how impairments to muscular or neuromotor systems may impact the ability to regulate stiffness in a contextually appropriate manner.…”
mentioning
confidence: 99%
“…Darainy et al (2004) through their measurements have shown that joint stiffness has a dynamic property and changes in the course of the movement. However, for the sake of simplicity, in this study the joint stiffness is assumed to be constant during movement, which implicitly means that the co-activation command is also supposed to be constant.…”
Section: Central Motor Commands and Joint Torquesmentioning
confidence: 99%
“…For example, when hitting a volley in tennis, the path followed by the arm before the event is not as critical as the precision of position at the point of contact with the ball [36]. It has been shown that any task learning requires the central nervous system to identify the input-output characteristics of the motor system for that specific task [8,21,35]. Thus, in the tennis volleying example, the central nervous system has to learn to carefully modulate racquet position and stiffness to control ball trajectory after impact.…”
Section: Introductionmentioning
confidence: 99%